A Study on Radial Properties of Hydrogenic Ions using Laguerre Polynomials - Pandu, Gerda; Pingak, Redi Kristian; Zicko Johannes, Albert; Seba Ngara, Zakarias (BULETIN FISIKA; Vol 23 No 2 (2022): BULETIN FISIKA August Edition, 2021)
A preliminary study has been carried out on the radial properties of the hydrogenic systems using the Laguerre polynomial. The aims of this study were to investigate radial properties of hydrogenic ions by evaluating the radial probability density, the most probable radial distance and the average distance of electron from the nuclei of hydrogenic ions. Based on the research results for Z=1 to Z=10 with the principal quantum number (n)=1 to 5, 150 radial function forms, 150 radial probability density, 150 most probable radial distance values and 150 electron average distance values were obtained. The most probable radial distance from the nucleus was compared with the Bohr model and showed the same results as the Bohr model.